Achieving Multidisciplinary Collaboration for the Creation of a Pulmonary Embolism Response Team: Creating a “Team of Rivals” - Kabrhel, Christopher (Semin Intervent Radiol, 2017)
Pulmonary embolism response teams (PERTs) have recently been developed to streamline care for patients with life-threatening pulmonary embolism (PE). PERTs are unique among rapid response teams, in that they bring together a multidisciplinary team of specialists to care for a single disease for which there are novel treatments but few comparative data to guide treatment. The PERT model describes a process that includes activation of the team; real-time, multidisciplinary consultation; communication of treatment recommendations; mobilization of resources; and collection of research data. Interventional radiologists, along with cardiologists, emergency physicians, hematologists, pulmonary/critical care physicians, and surgeons, are core members of most PERTs. Bringing together such a wide array of experts leverages the expertise and strengths of each specialty. However, it can also lead to challenges that threaten team cohesion and cooperation. The purpose of this article is to discuss ways to integrate multiple specialists, with diverse perspectives and skills, into a cohesive PERT. The authors will discuss the purpose of forming a PERT, strengths of different PERT specialties, strategies to leverage these strengths to optimize participation and cooperation across team members, as well as unresolved challenges.